El Uso De Las Tics Y El Desarrollo De Habilidades, Destrezas Cognitivas, Procedimentales Y Actitudinales En Los Docentes Del Colegio Nacional “5 De Junio” De La Ciudad De Babahoyo, Provincia De Los Ríos. - CARPIO CHELE, ÁNGELA (2014)
Regarding the issue of suggestive education we want for young people, I cannot but think that it will be impossible to outline the institution, if not clear the kind of teachers we need to be to support the learning and development of these young people. Although it has been shown that ICT is a social phenomenon of great importance that has transformed the lives of millions, has also acknowledged that its impact on education is far from its potential. In Latin America, based on the analysis of the experts, is not only a clear lag in access opportunities under equal conditions to those technologies, but also in relation to their educational uses. Apparently, under present conditions, and barring actions at all levels (political, educational, economic), ICT in our region will become a factor of inequality that perpetuates the cycle of social and educational exclusion that caught many of our children and youth. I am fully convinced that the introduction of ICT in education opens many possibilities, but also new demands. One of the most important challenges concerning the teaching task. The new demands on the teaching profession precisely claim that teachers are responsible for their students' technological literacy and mastery of a range of skills required in the context of the demands of the knowledge society. The question is, teachers are prepared for it?, Are we doing the right thing to ensure a proper teacher training?. Although the curriculum reforms of the last decade who boast of their foundations in constructivism, at least in the case of education systems in our region, still prevalent forms of education focused on declarative knowledge transmission and the learning assessments through multiple choice exams or almost literal retrieval of timely.